Pharmacological interventions for premature ejaculation: a mixed-treatment comparison network meta-analysis of randomized clinical trials. Issue 5 (October 2018) - Sridharan, Kannan; Sivaramakrishnan, Gowri; Sequeira, Reginald; Al-Khaja, Khalid
Abstract Premature ejaculation (PE) is the most common sexual dysfunction in men. The present study is a network meta-analysis of drugs used for treating PE. Electronic databases were searched for randomized controlled trials comparing medical interventions with either placebo or with other active drugs in patients with PE. Inverse variance heterogeneity model was used for mixed-treatment comparisons. Intravaginal ejaculatory latency time (IELT) and adverse events were the main outcome measures. A total of 44 studies were included in the meta-analysis. Dapoxetine 30 and 60 mg, tadalafil, sildenafil, paroxetine with sildenafil, topical lidocaine, dapoxetine 30 mg with mirodenafil, vardenafil, fluoxetine, and tadalafil, pindolol with paroxetine, tramadol, topical lidocaine with tadalafil, paroxetine with tadalafil, and topical eutectic mixture of local anesthetics were associated with a significant increase in IELT. Similarly, dapoxetine 60 mg, venlafaxine, fluoxetine, tramadol at 25, 50, and 100 mg, and combined fluoxetine and tadalafil were associated with an increased risk of adverse events. Dapoxetine 30 mg has a high likelihood of being the "best" in the interventional pool. Dapoxetine at 30 mg could be used as the first-line agent in the management of PE.